Keanekaragaman Makrozoobenthos di Sungai Way Umpu Kabupaten Way Kanan Provinsi Lampung - Arsitalia, Metari; Tugiyono, Tugiyono; Master, Jani; Susanto, G. Nugroho (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Way Umpu River, located in Way Kanan Regency, Lampung Province, is widely used by the local community and the waste products are ultimately disposed of into the river. This can cause a decrease in river water quality which can cause changes in the balance of the ecosystem, both biotic and abiotic. One of the organisms that can be used as a bioindicator is macrozoobenthos. This research aims to determine the diversity of macrozoobenthos as a bioindicator of water pollution quality. The method used was a survey method and sampling using Ekmen Grab at 6 sampling stations. Samples were taken 3 times in the left, middle and right bank areas of the river. Apart from that, water analysis was carried out in the form of physical parameters (temperature and TSS) and chemical parameters (pH, DO, COD, BOD). The data was then analyzed using the Diversity Index. The research results found 14 types of macrozoobenthos consisting of 5 phylum, namely Arthopoda, Mollusca, Porifera, Ciliophora, and Annelida. From the results of the analysis of the macrozoobenthos diversity index at station IV, it has a value of 0.56 ind/m2, which states that the location is heavily polluted. Physical and chemical factors show a significant correlation with macrozoobenthos diversity.